Novel mutation in the TMPRSS6 gene with iron‐refractory iron deficiency anemia. Issue 4 (August 2014) - Kodama, Koya; Noguchi, Atsuko; Adachi, Hiroyuki; Hebiguchi, Miwa; Yano, Michihiro; Takahashi, Tsutomu
Abstract Iron‐refractory iron deficiency anemia (IRIDA) is a rare autosomal recessive disease characterized by congenital hypochromic microcytic anemia, low transferrin saturation, low serum iron, normal–high serum ferritin, and increased hepcidin. This disease is caused by loss‐of‐function mutations in TMPRSS6 that lead to high hepcidin and result in severe anemia. We report our experience with an 11‐year‐old Japanese girl with hypochromic microcytic anemia, low serum iron, and high serum ferritin, with anemia that was refractory to the oral iron that was prescribed frequently from early childhood. Presence of high hepcidin suggested a diagnosis of IRIDA, which was eventually confirmed by identification of a novel homozygous mutation, p.Pro354Leu, in the TMPRSS6 gene. This case suggests that serum hepcidin should be routinely measured for differential diagnosis when patients with IDA are unresponsive to oral iron or have unusual clinical features.